Dysregulation of RNA-Binding Proteins in Amyotrophic Lateral Sclerosis - Xue, Yuan Chao; Ng, Chen Seng; Xiang, Pinhao; Liu, Huitao; Zhang, Kevin; Mohamud, Yasir; Luo, Honglin (Frontiers in Molecular Neuroscience, 2020)
Genetic analyses of patients with amyotrophic lateral sclerosis (ALS) have revealed a strong association between mutations in genes encoding many RNA-binding proteins (RBPs), including TARDBP, FUS, hnRNPA1, hnRNPA2B1, MATR3, ATXN2, TAF15, TIA-1, and EWSR1, and disease onset/progression. RBPs are a group of evolutionally conserved proteins that participate in multiple steps of RNA metabolism, including splicing, polyadenylation, mRNA stability, localization, and translation. Dysregulation of RBPs, as a consequence of gene mutations, impaired nucleocytoplasmic trafficking, post-translational modification, aggregation and sequestration by abnormal RNA foci, has been shown to be involved in neurodegeneration and the development of ALS. While the exact mechanism by which dysregulated RBPs contribute to ALS remains elusive, emerging evidence supports the notion that both a loss-of-function and/or a gain-of-toxic-function of these ALS-linked RBPs play a significant role in disease pathogenesis through facilitating abnormal protein interaction, causing aberrant RNA metabolism, and by disturbing ribonucleoprotein granule dynamics and phase transition. In this review, we summarize the current knowledge on the molecular mechanism by which RBPs are dysregulated and the influence of defective RBPs on cellular homeostasis during the development of ALS. The strategies of ongoing clinical trials targeting RBPs and/or relevant processes are also discussed in the present review.